PENGARUH PEMILIHAN JURUSAN DI SMA/MA TERHADAP MOTIVASI DAN HASIL BELAJAR MAHASISWA PADA MATA KULIAH KIMIA DASAR UNIVERSITAS MUARA BUNGO - Aswana (Pendidikan Matematika | STKIP YM Bangko, 2021)
The choice of department is very influencing, especially in Chemistry, which requires a high understanding of the basic concepts of learning chemistry and high creativity, so that motivation from students is needed to obtain satisfactory grades. This study aims to determine the effect of the choice of department in SMA / MA on student motivation and learning outcomes in learning Chemistry. This research is an experimental research. The study was conducted in 4 study programs, namely: mining, civil, agro-technology and animal husbandry, with a population of 38 students and a sample of 22 students. The research data were obtained from the final questionnaire of motivation and learning outcomes. The final questionnaire results and learning outcomes were analyzed using the normalitas test, homogeneity test and analysis of variance (ANOVA). The results showed the value of F = 85.78 and Sig 0.000 <0.05, which means that there is an effect of choosing a major on student motivation and learning outcomes.